Self-selection and earnings of emigrants from a welfare state - Panu Poutvaara; Martin D. Munk; Martin Junge (Institute for the Study of Labor (IZA), 2009)
Following a seminal contribution by Borjas (1987), a large literature has analyzed how income distribution and redistribution are related to immigration to various rich countries. In this paper, we take a look at the other side of the coin. We analyze emigration from Denmark, which is one of the richest and most redistributive European Welfare States. Using comprehensive register data on full population and a unique new representative survey, we analyze whether Danes with relatively high earnings ability favor countries with more unequal income distribution and lower taxes, like the United States.
urn:nbn:de:101:1-20090513427
Keywords: F22; J61; H2; 330; Migration; emigration; redistribution; brain drain; education; Auswanderung; Brain Drain; Hochqualifizierte Arbeitskräfte; Einkommensumverteilung; Sozialstaat; Dänemark